ISLAMIC BANKING - Kholid, Kholid; Adam, Saed M (Al-Thiqah : Jurnal Ilmu Keislaman, 2025)
Islamic banking, based on Sharia principles, aims to establish a fair and ethical financial system by prohibiting riba (usury), gharar (uncertainty), and maisir (gambling). This study examines the challenges of Islamic banking literacy, its implementation in financial sectors, and its alignment with Qur'anic and Hadith principles. Using a qualitative approach, the research incorporates literature reviews and case studies to evaluate financial literacy levels and identify barriers to adoption. The findings indicate that limited public knowledge and misconceptions about Islamic banking hinder its broader acceptance. Additionally, regulatory constraints and inadequate dissemination of Islamic banking principles contribute to these challenges. To address them, structured educational programs, policy interventions, digital literacy campaigns, and collaborative initiatives between financial institutions and academia are recommended. Enhancing financial literacy can increase public participation in Sharia-compliant banking, ensuring sustainability in modern economies. This study underscores the importance of an inclusive and ethical financial system, advocating for broader awareness and engagement with Islamic banking principles as a means to develop a more just and equitable economic framework.